Methane Production in Ruminant Animals - Zaman, M.; Kleineidam, K.; Bakken, L.; Berendt, J.; Bracken, C.; Butterbach-Bahl, Klaus; Cai, Z.; Chang, S.X.; Clough, T.; Dawar, K.; Ding, W.X.; Dörsch, P.; et al. (Springer, 2021)
Agriculture is a significant source of GHGsglobally and ruminant livestock animals are one of the largest contributors to these emissions, responsible for an estimated 14% of GHGs (CH 4 and N 2 O combined) worldwide. A large portion of GHG fluxes from agricultural activities is related to CH 4 emissions from ruminants. Both direct and indirect methods are available. Direct methods include enclosure techniques, artificial (e.g. SF 6 ) or natural (e.g. CO 2 ) tracer techniques, and micrometeorological methods using open-path lasers. Under the indirect methods, emission mechanisms are understood, where the CH 4 emission potential is estimated based on the substrate characteristics and the digestibility (i.e. from volatile fatty acids). These approximate methods are useful if no direct measurement is possible. The different systems used to quantify these emission potentials are presented in this chapter. Also, CH 4 from animal waste (slurry, urine, dung) is an important source: methods pertaining to measuring GHG potential from these sources are included.